Reasons why not all Danish patients with muscle invasive bladder cancer receive neoadjuvant chemotherapy before radical cystectomy. (4th July 2019) - Nielsen, Ninna; Wrist Lam, Gitte; Fabrin, Knud; Holt, Per; Thind, Peter Ole; Jensen, Jørgen Bjerggaard
Abstract: Background: Danish guidelines on muscle invasive bladder cancer (MIBC) recommend neoadjuvant chemotherapy (NAC) for non-metastatic patients fit for cisplatin-based chemotherapy. The current indication is urothelial MIBC in patients less than 75 years old with no metastasis on imaging and normal renal function (GFR ≥ 60 ml/min). Data from the Danish Bladder Cancer Database (DaBlaCa-Data) reveals that only 40–50% of MIBC patients below 75 years of age receive NAC prior to cystectomy. The aim of this study was to clarify the reasons why the remaining patients do not receive NAC. Methods: Individual patient data were collected retrospectively from all five Danish urologic departments performing cystectomies. Patients fulfilling the inclusion criteria: MIBC at TURBT, age less than 75 years old and subsequent cystectomy were included and registered by the specific reason why NAC was not given. In total, 449 patients met the age- and T-stage criteria for NAC in the period September 2014 through August 2017. Results: In total, 274 patients (61.0%) received chemotherapy. Of the 175 patients who did not receive NAC, 140 patients (80%) were not fit for cisplatin and 35 patients did not receive NAC and had no specific contraindication. This ranged from 0–18% of included patients in the different centres. The main reason was patient refusal (97%). Interestingly, this ranged from 0–50% of patients not receiving NAC when comparing the five centres. Conclusion: These findings underline the need for proper patient information in order to get a uniform treatment strategy between centres.